Kyrle's disease associated with HIV infection, diabetes, and chronic kidney disease - Geysa Maria Nogueira Farias; José Reginaldo Pinto; Juliana Carneiro Melo; Lara Gurgel Fernandes Távora; Danielle Malta Lima; Fernanda Judith Viana Correia; Geraldo Bezerra da Silva Júnior (Wolters Kluwer Medknow Publications, 2018)
Kyrle's disease (KD) is a rare skin pathology characterized by transepidermal elimination of abnormal keratin. The aim of this article is to report a rare case of KD associated with diabetes mellitus, chronic kidney disease, and HIV. A 51-year-old male patient complained of diarrhea for 8 months. He was submitted to HIV testing, which showed a positive result. He started antiretroviral therapy with zidovudine, lamivudine, and lopinavir. The diagnostic investigation was negative for opportunistic diseases. After 2 months, skin lesions started appearing, characterized by hyperchromic, pruritic macules and papules distributed in the trunk, back, and upper limbs. He also developed erythematous, scaly lesions in the facial region. A biopsy of the skin was performed, of which histopathological report consisted of perforating disorder, favoring a diagnosis of KD. Treatment with keratolytic soap (Actine) was started, with skin lesion improvement. In this reported case, it is possible that, in addition to diabetes and renal failure, HIV infection played an important role in the genesis of the lesions.